Nilai-Nilai Filosofi Ornamen Oktagon Kaligrafi Pada Masjid Muhammad Cheng Hoo Di Kecamatan Pandaan Kabupaten Pasuruan - Fendi Tri Akbar,; I Wayan Arsana, (Student Scientific Creativity Journal, 2025)
This study refers to the philosophical values of calligraphy octagonal ornaments at the Muhammad Cheng Hoo Mosque in Pandaan District, Pasuruan Regency. The objectives of this study are: 1. To find out the meaning of calligraphy octagonal ornaments in the Muhammad Cheng Hoo Mosque 2. To find out the philosophical value contained in the calligraphy octagonal ornaments at the Muhammad Cheng Hoo Mosque. The method used in this study is a qualitative method. The data collection techniques used are observation, interview, and documentation methods. The results of this study show that the meaning of calligraphy octagonal ornaments has a meaning that can be associated with one pillar of Islam. Because it shows unity and balance in carrying out religious commands and as the meaning of the five levels, in Islamic teachings are shahada, prayer, fasting, zakat and hajj as well as the meaning of blessings and abundance of sustenance. The philosophical value of octagonal ornaments has the meaning of balance, harmony and protection as well as the philosophical value of red and yellow colors in calligraphy octagonal ornaments, red is interpreted as joy, strength, and courage while yellow is interpreted as blessings and abundance of sustenance.